Behavior Mapping Study of The Layout of Drug Service Room in Outpatient Pharmacy of X Hospital - Yulianto, Wahyu; Zuhriyah, Lilik; Haripradiantoi, Tito (Universitas Muhammadiyah Yogyakarta, 2024)
The quality of pharmaceutical services is related to patient satisfaction and the short waiting times for their accomplished drug in pharmacy installation. This research was conducted to describe the prescription service process in the outpatient pharmacy at X Hospital by observing the flow of drug dispensing and officer movement along with the time required for the process, with the environment behavior study and value stream mapping as the observation method. This action research was conducted by collecting qualitative and quantitative data. Data collection was carried out by observation (time allocation, time for drug service activities), interviews, focus group discussion (FGD), and Behavior Mapping. The results of value stream mapping showed that non-value added was greater than value-added, 78.5% versus 21.5%. Behavior mapping showed a physical trace in a stack of prescription files in all POSs during the service process. The longest process time occurred at post 4, which is during drug preparation, while the longest interval time was interval time 4, which is waiting for the re-check process. Other factors cause the waiting time for drug services to be lengthened. The spatial structure of pharmacy depot block A was less effective. The waiting time was still long. The researchers suggest that the space be regulated again and continued to the next action research cycle, up to the effective drug services, so that the waiting times can be short.